Negativni lomni količnik - Strnad, Janez (Obzornik za matematiko in fiziko, 2008)
Lately in physics journals negative refraction is often discussed. In this article a simple description of the basics of the phenomena and its background is given.
Keywords: fizika; lomni količnik